Efficacy of different formulations of nystatin in an experimental model of oral candidiasis in sialoadenectomized rats - Mario Pérez-Sayáns; Renee Beiro-Fuentes; Eva M. Otero-Rey; Cintia Micaela Chamorro-Petronacci; Pilar Gándara-Vila; Jose Manuel Somoza-Martín; Abel García-García; Andrés Blanco-Carrión (Elsevier, 2021)
Background/purpose: Oral candidiasis is the most common fungal infection of the oral cavity and has become a focus of attention in recent years because of its association with highly topical immunosuppressive conditions. The aims of this study were to determine the value of microbiological, clinical and histological parameters of Candida albicans colonisation of the dorsal tongue surface as indicators of disease severity, and to evaluate therapeutic response to different formulations of nystatin. Materials and methods: We used 84 males, 2-month-old Sprague-Dawley sialoadenectomized rats. Different formulations of nystatin were used to evaluate the therapeutic response. The animals were randomized to 2 groups with each of 42 animals and received the experimental treatments from day 17-22. Results: 100% of the rats showed evidence of infection. At 5 and 10 days of starting treatment with nystatin + chitosan, and at 10 days of starting nystatin + orabase, the number of animals with positive dorsal tongue culture decreased significantly (p < 0.05), acting the Nystatin + chitosan more rapidly against Candida. In the control group, the percentage of normal papillae on day 22 and 27 was 83.33% (SD = 1.50) and 79.08% (SD = 2.30), respectively. Significant differences were observed in the mean O'Grady score at 5 and 10 days (p < 0.0001). Conclusion: The model has been shown to be effective in inducing infection, and that the combination of nystatin and chitosan yielded the best therapeutic outcomes at both 5 and 10 days after infection.